2016
DOI: 10.1007/s00520-016-3364-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life amongst lymphoma survivors in a developing country

Abstract: Purpose The survival for patients with lymphoma has improved over the past decades with the introduction of novel agents. Quality of life of these survivors is now being studied with focus on minimising the late effects of chemotherapy and improving psychosocial support. This study aims to determine the prevalence of anxiety and depression of lymphoma survivors and to investigate the possible association between these disorders and quality of life. Methods Patients with previous diagnosis of lymphoma who remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…In our study, the prevalence of anxiety (17%) and depression (12.3%) found in the total sample of lymphoma survivors is, however, in line with the data found in the literature ( Hjermstad et al, 2004 ; Thompson et al, 2010 ; Wang et al, 2013 ), underlining how the survivorship condition of this specific illness is characterized by consequences that increase the levels of psychological distress ( Korszun et al, 2014 ) compared with other types of tumors ( Joshy et al, 2020 ). In accordance with what was reported in the literature, our sample of lymphoma survivors showed higher anxiety intensity than the depression intensity ( Loge et al, 1997 ; Gil-Fernández et al, 2003 ; Aksnes et al, 2007 ; Daniëls et al, 2014 ; Ng et al, 2016 ; Husson et al, 2017 ; Magyari et al, 2017 ; Bøhn et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the prevalence of anxiety (17%) and depression (12.3%) found in the total sample of lymphoma survivors is, however, in line with the data found in the literature ( Hjermstad et al, 2004 ; Thompson et al, 2010 ; Wang et al, 2013 ), underlining how the survivorship condition of this specific illness is characterized by consequences that increase the levels of psychological distress ( Korszun et al, 2014 ) compared with other types of tumors ( Joshy et al, 2020 ). In accordance with what was reported in the literature, our sample of lymphoma survivors showed higher anxiety intensity than the depression intensity ( Loge et al, 1997 ; Gil-Fernández et al, 2003 ; Aksnes et al, 2007 ; Daniëls et al, 2014 ; Ng et al, 2016 ; Husson et al, 2017 ; Magyari et al, 2017 ; Bøhn et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Above all, when comparisons are made between series of a given cancer localization or between cancer localizations, methodologies and instruments for fatigue assessment used often differ. In recent studies focusing on lymphomas, data from HL and NHL survivors were pooled when reporting on long-term fatigue [912]. We had the opportunity to develop two cross-sectional surveys with the aim to evaluate rehabilitation, health status, and long-term fatigue in survivors of lymphomas who participated in clinical protocols conducted by two European cooperative groups.…”
Section: Discussionmentioning
confidence: 99%
“…8 Moreover, a study from Malaysia revealed that blood cancer patients had higher level of anxiety, depression, fatigue, pain, insomnia influencing their health outcomes. 9 Another study conducted in Iran reported negative significant correlation between physical symptoms like fatigue, pain, and quality of life of cancer patients. Thus, it was suggested to design appropriate interventions such as counseling program which can help to improve symptoms, depression, and quality of life among cancer patients.…”
Section: Introductionmentioning
confidence: 99%